More than just characters in a story: effective and meaningful involvement of young people in mental health research. Issue 1 (24th January 2019) - MacSweeney, Niamh; Bowman, Sarah; Kelly, Clare
Abstract : Purpose: The story of youth mental health remains poorly understood. To truly progress our understanding of youth mental health, we must shift our focus from one in which young people are the subjects, or "characters", of research efforts to one in which they are active agents, or "authors". This change in dynamic falls under the banner of public and patient involvement (PPI), a growing movement that emphasises the meaningful involvement of the public in health research. The paper aims to discuss these issues. Design/methodology/approach: Here, the authors aim to stimulate this shift in focus by describing emerging practices of youth involvement in paediatric research and outlining how such practices can be extended to the domain of youth mental health. In particular, the authors highlight Young Persons' Advisory Groups (YPAG), through which young people can be involved in an active, meaningful and mutually beneficial manner, at each step in the research life cycle. Findings: A YPAG comprises young people who act as research partners, providing guidance on a range of activities. In the health domain, YPAGs have provided fresh perspectives, generated valuable knowledge and changed attitudes about youth involvement in research. Moreover, they provide young people with genuine opportunities to shape research so that it addresses issues they encounter in their everyday lives. Originality/value: The establishment of youth mental health YPAGs will enhance the authors' research questions, design, delivery and impact. The authors outline how researchers can embrace PPI and work together with young people to tell a different story of youth mental health.